The role of village development on stunting prevalence reduction in Eastern Indonesia - Indriana, Intan Solikhah; Hartarto, Romi Bhakti; Fadhila, Tiara; Nugraha, Gilang Adi (Universitas Muhammadiyah Yogyakarta, 2024)
Stunting has become a global priority in addressing health disparities among children. The study aims to investigate the autonomy of villages in reducing the prevalence of stunting in eastern Indonesia. The research data coverage is derived from sources with high credibility in Indonesia. The prevalence of stunting is obtained from the Indonesian Nutrition Status Survey by the Ministry of Health, while the Village Development Index is sourced from the Ministry of Villages. Panel data from 13 provinces in Eastern Indonesia for 2015-2022 are estimated using the Random Effect Model through the Generalized Least Squares method. The findings indicate that the Village Development Index significantly influences the reduction of stunting rates. This highlights the importance of local empowerment strategies in combating health disparities. Furthermore, the decrease in unmet Family Planning (FP) service needs, the decline in early marriages under 18 years, and the higher years of education contribute significantly to the reduction of stunting prevalence. This underscores the interconnection between social determinants and child health outcomes.